Microbial and Geochemical Dynamics of an Aquifer Stimulated for Microbial Induced Calcite Precipitation (MICP) - Ohan, J. A.; Saneiyan, S.; Lee, J.; Bartlow, Andrew W.; Ntarlagiannis, D.; Burns, S. E.; Colwell, Frederick S. (Frontiers in Microbiology, 2020)
Microbially induced calcite precipitation (MICP) is an alternative to existing soil stabilization techniques for construction and erosion. As with any biologically induced process in soils or aquifers, it is important to track changes in the microbial communities that occur as a result of the treatment. Our research assessed how native microbial communities developed in response to injections of reactants (dilute molasses as a carbon source; urea as a source of nitrogen and alkalinity) to promote MICP in a shallow aquifer. Microbial community composition (16S rRNA gene) and ureolytic potential (ureC gene copy numbers) were also measured in groundwater and artificial sediment. Aquifer geochemistry showed evidence of sulfate reduction, nitrification, denitrification, ureolysis, and iron reduction during the treatment. These geochemical changes corresponded to evidence of microbial taxa present in the groundwater that are known to be capable of the same biological processes as well as precipitation of calcite. We detected an increase in the number of ureC genes in the microbial communities at the end of the injection period, suggesting an increase in the abundance of microbes possessing this gene as needed to hydrolyze urea and stimulate MICP. We identify geochemical and biological markers that highlight the microbial community response when in-situ calcite precipitation occurs and these signatures can be used to assess progress of MICP.